Improvement of SD Negeri 2 Bojongmengger school library services by Customer Relationship Management (CRM) design - Nanda Khaerunnisa Syafitri; Hana Silvana; Dini Suhardini (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
The widespread COVID-19 pandemic has had an impact on the realm of education. The enactment of the Learning From Home (LFH) policy has reduced activities carried out in schools. The school library at SDN 2 Bojongmengger was also affected and began to have fewer visitors, even though limited face-to-face activities were re-implemented at school. Therefore, a Customer Relationship Management (CRM) strategy is needed to properly maintain the school library's function and role. CRM strategy is an effort to attract students and teachers as school library customers to visit the library. The method used in this service is the service improvement method with the results of research and development. With the potential and problem analysis process steps, data analysis, and product design. Based on the results that have been implemented, the results show that the design of the CRM strategy in the school library can be carried out conventionally first by collecting needs data, data processing, collection development, user education, competitions, and rewarding after that it can be carried out developing CRM in a digital direction through the use of media Instagram.   Abstrak Pandemi COVID-19 yang meluas menyebabkan berdampak pada ranah pendidikan. Dengan diberlakukannya kebijakan Belajar Dari Rumah (BDR) yang menyebabkan berkurangnya kegiatan yang dilaksanakan di sekolah. Perpustakaan sekolah di SDN 2 Bojongmengger pun ikut terdampak dan mulai minim pengunjung meski sudah kembali diberlakukan kegiatan tatap muka terbatas di sekolah. Oleh karena itu, agar dapat mempertahankan fungsi dan peran perpustakaan sekolah dengan baik, diperlukan sebuah strategi Customer Relationship Management (CRM). Hal ini sebagai upaya untuk dapat menarik minat siswa dan guru sebagai pelanggan perpustakaan sekolah untuk dapat mengunjungi perpustakaan. Metode yang digunakan dalam pengabdian ini adalah metode peningkatan layanan dengan hasil research and development. Dengan langkah proses analisis potensi dan masalah, analisis data dan membuat desain produk. Berdasarkan hasil yang telah dilaksanakan, didapatkan hasil bahwa rancangan strategi CRM di perpustakaan sekolah dapat dilaksanakan secara konvensional terlebih dahulu dengan kegiatan pendataan kebutuhan, pengolahan data, pengembangan koleksi, user education, perlombaan dan rewarding setelah itu dapat dilakukan pengembangan CRM ke arah digital melalui pemanfaatan media sosial instagram. Kata Kunci: Belajar dari Rumah; BDR; Customer Relationship Management; CRM; Pandemi COVID-19; Peningkatan Layanan;  Layanan Perpustakaan Sekolah.